Analisis Kata Tanya (Adawat Istifham) Dalam Surat Ali Imran: Analisis Kata Tanya (Adawat Istifham) - Nurkholis; Muhammad Wisnu Khumaidi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2019)
Interpretation of adawat al-Istifham (question word) contained in Surah Ali-Imran and its relevance to qowaid al arobiyah is a discussion that is laden with meaning and purpose in the Qur'an. The i'jaz values that is never subsided studied by mufasirin salaf and kholaf to prove the miracle of the Qur’an in terms of language and letters. Inside theQur’an, it is not only implying the rules of nahwu and shorof but also has implications for law and interpretation. With the writing, we can find out the forms of usage as well as other meanings of each adawat al-Istifham (question word), and now it is still largely unknown. The results of this study proved the number and variety of meanings of adawat al-Istifham in the Al-Qur'an Surah Ali-Imran. The review used in this study is a syntactic review that explains the function and syntax of each adawat al-Istifham used in Surah Ali Imran.